Integrating Obesity and Diabetes Management: A Narrative Review of Multilevel Strategies - Hamzah, Pratiwi Nasir (PT.Mantaya Idea Batara, 2024)
Background: Obesity and type 2 diabetes mellitus (T2DM) are global public health challenges that frequently coexist due to overlapping metabolic and inflammatory pathways. This narrative review examines the bidirectional relationship between these conditions and evaluates multidisciplinary strategies for integrated prevention and management. Using literature from Scopus and ScienceDirect (2014–2024), the review includes studies that explore pathophysiological connections, lifestyle-based and pharmacological interventions, and public health policy innovations. The findings highlight the central role of visceral adiposity in insulin resistance and beta-cell failure, necessitating integrated treatment approaches. Multidisciplinary programs that combine dietary, behavioral, and technological interventions show promising outcomes in both weight and glycemic control. Policy interventions such as sugar-sweetened beverage taxation and front-of-pack labeling have contributed to improved population-level health behavior. Furthermore, community-based strategies, particularly in low- and middle-income countries (LMICs), offer culturally relevant and scalable solutions. Despite these successes, challenges remain in achieving sustainability, ensuring equitable access, and adapting interventions to local contexts. This review underscores the need for harmonized clinical, behavioral, and policy approaches, and calls for further research into long-term outcomes, scalability, and cost-effectiveness of integrated strategies for addressing the dual burden of obesity and diabetes